POPULASI DAN SERANGAN KUTU PUTIH PEPAYA, PARACOCCUS MARGINATUS (HEMIPTERA: PSEUDOCOCCIDAE) PADA TANAMAN PEPAYA DI DAERAH DATARAN RENDAH SUMATERA SELATAN - Rosdah Thalib .; Rossi Fachrullah Rozi; Triani Adam .; Khodijah . .; Siti Herlinda . (Universitas Lampung, 2014)
Populations and damage by the papaya mealybug Paracoccus marginatus (Hemiptera: Pseudococcidae) on papaya inlowland areas of South Sumatera. One of the main problems in papaya cultivation today is the presence of a newlyintroduced pest, the white papaya mealybug, Paracoccus marginatus (Hemiptera: Pseudococcidae). This study aimed toobserve the mealybug populations and its damage percentage in papaya plants and to identify its host plants in SouthSumatera. The study was carried out on the fruit and vegetable producing area in Indralaya, South Sumatera. The survey wasconducted on papaya plantation plots with a minimum size of 1000 m2. Data from the observation indicated that populationsof P. marginatus on papaya fruit were not significantly different to those on papaya leaves, except for the first observation inthe rainy season. In general, the percentages of mealybug damages were not affected by the season and the percentages ofdamage on the leaves were not different from those on the fruits of the papaya plants. Inventory of P. marginatus host plantson the area resulted in a total of 12 species of host plants dominated by dicotyledonous plant species. The host plants werefrom 11 families, i.e. Anacardiaceae, Caricaceae, Cucurbitaceae, Euphorbiaceae, Fabaceae, Myrtaceae, Rosaceae, Rutaceae,Sapindaceae, Sapotaceae, and Solanaceae.